2009
DOI: 10.5551/jat.1081
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Soluble SR-PSOX/CXCL16 as a Biomarker for Acute Coronary Syndrome -Comparison with High-Sensitivity C-Reactive Protein

Abstract: Aim: Diagnostic values of soluble SR-PSOX/CXCL16 (sSR-PSOX/CXCL16), a receptor for atherogenic oxidized LDL and a membrane-anchored chemokine for CXCR6-positive lymphocytes, for acute coronary syndrome (ACS) were evaluated. Methods: We examined 106 patients undergoing coronary angiography (CAG); 17 patients with ACS and 89 patients without ACS (non-ACS) including stable angina. Circulating sSR-SPOX/CXCL16 was measured in peripheral venous blood by sandwich ELISA. Results: Age, gender, prevalence of diabetes or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Post-procedural elevation of cardiac biomarkers, such as troponin-T (TnT), has been recognized to be a relatively common phenomenon following successful percutaneous coronary interventions (PCIs) [1][2][3][4] . Previous studies have demonstrated that the elevation of TnT predicts long-term mortality [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Post-procedural elevation of cardiac biomarkers, such as troponin-T (TnT), has been recognized to be a relatively common phenomenon following successful percutaneous coronary interventions (PCIs) [1][2][3][4] . Previous studies have demonstrated that the elevation of TnT predicts long-term mortality [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…27 Other recent studies described CXCL16 as a positively associated marker of inflammation and progression of coronary atherosclerosis, particularly ACS. 28,29 Furthermore, increased CXCL16 levels were demonstrated to be associated with long-term mortality in patients with ACS. 10 Although platelets are known to be the major players in the pathogenesis of atherothrombosis, 5 nothing is known about the influence of CXCL16 on platelet function.…”
mentioning
confidence: 99%
“…It is known as a scavenger receptor that binds phosphatidylserine and oxidized lipoproteins (Mitsuoka et al, 2009). Garcia et al (2007) found that in glomerular nephritis, CXCL16 was expressed in glomerular endothelial cells under the stimulation of pro-inflammatory factors, while IL-1β promoted CXCL16 expression in mesangial cells.…”
Section: Discussionmentioning
confidence: 99%